Prevalence and Clinical Manifestations of Cattle Foot and Mouth Disease in Wajak Subdistrict, Malang Regency - Adikara, Yuanara Augusta Rahmat; Tuska, Habib Syaiful Arif; Brahmantya, Chandra; Karaman, Yulinar Risky; Abdurrahman, Farid; Mufa, Romy Muhammad Dary; Atmaja, Baluh Medyabrata; Widodo, Wahyu (Biotropika: Journal of Tropical Biology, 2026)
Foot and Mouth Disease (FMD) is a highly contagious viral disease affecting cloven-hoofed animals with significant economic implications. Following a disease-free status since 1986, Indonesia experienced a resurgence of outbreaks in 2022, including in the Malang Regency. This study aimed to analyse the prevalence and clinical manifestations of FMD in the cattle population of Wajak Subdistrict, Malang Regency. The research employed a cross-sectional observational design with a total sample of 405 dairy cattle from This study involved 405 dairy cattle from various farms (n=15) in Wajak Subdistrict, Malang Regency, selected based on outbreak history and accessibility. Comprehensive clinical examinations were conducted to identify FMD manifestations using a severity-based scoring system. Serological confirmation using Non-Structural Protein (NSP) test kits was performed on a subsample of 20 animals to detect FMD virus exposure. Results indicated an FMD case prevalence of 1.2% (5 out of 405 animals), with all cases exhibiting complete clinical manifestations, including high fever (average 40.62°C), vesicular lesions in the oral cavity (score 2), lesions on feet (score 1), hypersalivation (score 2), severe appetite loss (60% score 4), and milk production decline with varying severity. The NSP test kit examination of the subsample showed 100% positive results, indicating widespread FMD virus circulation in the study area, despite clinical manifestations appearing in only a small proportion of the population. This study demonstrates that although the clinical FMD case prevalence is relatively low (1.2%), virus circulation remains high in the cattle population of the Wajak Subdistrict, indicating the presence of subclinical infections. Comprehensive FMD control strategies require a combination of mass vaccination, strict biosecurity measures, and continuous surveillance, including subclinical infection detection.